2018
DOI: 10.1177/1476750318790797
|View full text |Cite
|
Sign up to set email alerts
|

This is our home: Initiating participatory action housing research with refugee and immigrant communities in a time of unwelcome

Abstract: Community Voices for Housing Equality is a participatory action research group made up of community leaders and social workers whose aim is to address inequality and unfairness in housing by centering the voices of tenants. In this article, the core Community Voices for Housing Equality research team narrates and presents findings from phase one of the project, focused on the experiences of tenants with refugee and immigrant background in Salt Lake County, UT. The authors explain how the project emerged and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies have found that undocumented immigrants live in poorer quality, overcrowded housing and face more housing challenges than do documented immigrants and native-born renters (Hall & Greenman, 2013 ; McConnell, 2017 ). Once housing is secured, unscrupulous landlords may take advantage of immigrants who do not know their legal rights and protections ( Byrne et al, 2018 ).…”
Section: Immigrant Family Strengths and Economic Realities Pre-covid-19mentioning
confidence: 99%
“…Studies have found that undocumented immigrants live in poorer quality, overcrowded housing and face more housing challenges than do documented immigrants and native-born renters (Hall & Greenman, 2013 ; McConnell, 2017 ). Once housing is secured, unscrupulous landlords may take advantage of immigrants who do not know their legal rights and protections ( Byrne et al, 2018 ).…”
Section: Immigrant Family Strengths and Economic Realities Pre-covid-19mentioning
confidence: 99%